PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYELUNDUPAN PAKAIAN BEKAS OLEH PENYIDIK PEGAWAI NEGERI SIPIL BEA DAN CUKAI DI KABUPATEN INDRAGIRI HILIR - Nurviyani '; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Smuggling in essence can be interpreted as an act of importing, exporting, transfer between island do not care the laws and regulations that apply , or do not comply with customs formalities are required by law, used clothing imports have been banned from entering Indonesia since 1982 by the Ministry of trade and Cooperatives No. 28 / Kp / I / 82 determined that the former is used clothing items can not be imported or entered into Indonesia. Civil Servant Investigators (investigators) Customs and Excise given sufficient authority to investigate both criminal offenses and customs offenses, including the crime of smuggling. But in the case of smuggling of used clothing no instance that enter into the process of investigation, while sales of used clothing is increasing. As for the objectives of this thesis, namely: First, law enforcement is carried out by investigators of Customs and Excise against the smuggling of used clothing, Second, do not factor investigation, Third, Law Enforcement investigators who carried out are in accordance with the legislation.The conclusion of this study is the first acts undertaken by Customs and Excise investigators to eradicate smuggling used clothing in the form of law enforcement, preventive and repressive. Namely preventive law enforcement surveillance and patrols, namely repressive law enforcement to arrest and seizure. Both of cause is not an investigation into alleged criminal acts of smuggling of used clothing is the evidence that had been destroyed prior to the investigation. Third, law enforcement against the smuggling of used clothing by investigators not in accordance with the rules and regulations perudang for goods from the arrests have been destroyed before the investigation.Suggestions author of the issues examined are first, Customs and Excise Tembilahan an understanding of the community to the impact of second-hand clothes, Second Investigation on smuggling of used clothing should be appropriate to follow the legal process in accordance with the criminal justice system in Indonesia, the Third Law Enforcement by investigators Bea and Excise against the smuggling of used clothing in Indragiri Hilir must be made reference to the provisions of Customs law applicable.Keywords: Law Enforcement – The Crime Of Smuggling – Use Clothing